Is there a relationship between substance use disorders and violent offending? : a case study of Rimutaka and Wellington male prisoners : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Rehabilitation at Massey University - Jones, Amanda (Massey University, 2007)
New Zealand imprisonment per capita rates are second only to the USA with continued growth expected in the next decade. Previous research and extensive personal work experience within the prison system suggests that there is a connection between Substance Use Disorders (SUDs) and crime. The main object of this study was to investigate and ascertain if there is a relationship between occurrences of SUDs and violent offending. This is a complex question, as it is unlikely that SUDs are the only determinants of violent offending. Demographics, ethnicity, education and other environmental and psychological factors will also be contributing factors. The current study tests SUDs and 'other factors' to see if a relationship exists. Two hundred prisoners from Rimutaka and Wellington Prisons were randomly selected from a possible sample size of 850. The 102 respondents who chose to take part in the study were administered the Substance Use Disorders Diagnostic Schedule (SUDDS-IV). Seventy of these 102 prisoners were in prison for having committed a violent offence. A demographic questionnaire followed the psychometric test. Surprisingly, SUDs (both substance abuse and substance dependence), were not found to be statistically more significant in prisoners that had offended violently. Overall, SUDs were found in 99% of the entire population. Eighty-four percent diagnosed with substance dependence and a further 8.8% with substance abuse. Only 6.9% did not have a SUD at all. Fifty-eight percent of the sample investigated identified themselves as Maori, 26.5 European and 13.7% Pacific Islanders. This study found that those imprisoned for a violent conviction were more likely to be Maori. In addition, it illustrated that the prisoners convicted for violence were more likely to have only two years secondary school education or less. Evidence also shows that Maori studied were less likely to be educated. However, such findings require more validation for use as evidence in prisoner research. Further research could include a qualitative approach with emphasis on Maori with limited education and a propensity to be violent. This research would be beneficial if directed towards the unique lives of New Zealand prisoners, their families and specifically the children of the established offenders. The main objective would be to provide information about the next generation of violent offenders. The data and intelligence gathered could be then utilised to better manage and treat violent offenders.
Keywords: New Zealand; Substance use; Violent offenders; Prisoners